Desain Peta Strategi dan Pemantauan Sasaran Mutu Studi Kasus di Perusahaan Indoor Furniture - Elizabeth Winona Felicia Indranatan; I Nyoman Sutapa (Jurnal Titra, 2020)
Performance measurement is important for a company to assess the achievement of targets from its departments. Research was done at an international furniture company. The company is currently measuring work performance using quality target that have been set by management. The Balanced Scorecard (BSC) uses quality objectives and Key Performance Indicator (KPI) as the basis for measurement. The BSC design is carried out not only measures the financial aspects, but also non financial aspects. The BSC design is carried out in five departments, namely Quality Assurance (QA), Human Resource Development (HRD), production P1, logistics, and purchasing department. The result of design is the strategy map and the causal relationship between quality objectives. The causal relationship between quality objectives shows the quality objectives with the longest chain and the quality objectives which is the final goal. Analysis is carried out on the result of monitoring of quality targets with the longest chain so that problems are identified and can provide proposed solutions.